Harnessing Serratia marcescens: A Dual Role as Biocontrol Agent Against Fusarium oxysporum f.sp. melongenae and Heteroauxin Producer - Khalimi, Khamdan; Pranatayana, Ida Bagus Gde; Batin, Charlie B (International Journal of Biosciences and Biotechnology; Vol 11 No 2 (2024): International Journal of Biosciences and BiotechnologyDO - 10.24843/IJBB.2024.v11.i02.p05, 2024)
Pathogens and plant growth factors significantly influence plant growth and development. This study aims to investigate the potential of Serratia marcescens as a biocontrol agent against Fusarium oxysporum f.sp. melongenae and its capability as a heteroauxin producer. Antagonistic tests of S. marcescens against F. oxysporum f.sp. melongenae were conducted using a dual culture method, while the antifungal activity of S. marcescens extract was assessed through the disk diffusion method. Salkowski's colorimetric test was performed both in vitro and in situ to analyze heteroauxin compounds, further identified by GC-MS. Results demonstrated that all four tested S. marcescens strains could inhibit the growth of F. oxysporum f.sp. melongenae, with inhibition rates ranging from 93.76% to 94.02% compared to the control. These strains produced heteroauxin and its derivatives, including 3-methylindole, salicylic acid, and indole-3-acetic acid methyl ester, as confirmed by GC-MS. This study concludes that the examined S. marcescens strains are promising biocontrol agents and heteroauxin producers, highlighting their potential for sustainable agriculture practices.